The Economics of Charitable Activities in Canada - Tian, Wenjie (Université d'Ottawa / University of Ottawa, 2026)
This thesis explores how macroeconomic conditions and local community characteristics shape charitable behaviour and the dynamics of charities in Canada. It comprises three chapters that analyse private giving, government funding, and the location decisions of charities. Using the Canada Revenue Agency's Registered Charity Information Returns (Form T3010), macroeconomic indicators, and census data from 1990 to 2021, it combines time-series, panel, and spatial analyses to examine funding flows and organisational behaviour in response to both national economic fluctuations and neighbourhood-level socio-economic variation. The first two chapters focus on the relationship between macroeconomic conditions and charitable giving and funding. Chapter One analyses the relationship between business cycles and private donations across charitable fields, building on and extending the approach of List and Peysakhovich (2011). Using autoregressive distributed lag (ARDL) and nonlinear ARDL (NARDL) models, the chapter finds that total donations and giving to Foundations increase with GDP growth, while donations to Relief of Poverty respond countercyclically. Panel analysis across ten provinces confirms the procyclicality of total donations and giving to Religion, and the countercyclicality of giving to Relief of Poverty during downturns. Asymmetric patterns are evident in Education at the national level and in Relief of Poverty at the provincial level. Chapter Two examines how government funding to charities responds to macroeconomic conditions, using ARDL, NARDL, and panel models across federal, provincial, and municipal levels. The findings show that funding patterns vary by government tier, charity field, and business cycle phase. Federal funding is generally countercyclical, stabilising key sectors such as Relief of Poverty and Religion. In contrast, provincial and municipal funding is largely procyclical, targeting local priorities like Community and Health. Religion funding increases during downturns and remains stable during upturns, reflecting its role in supporting social cohesion. Education and Community funding rise with economic expansions, while Arts funding increases during contractions. In the Education sector, public funding closely follows GDP growth, with no clear evidence of crowding-in or crowding-out by private donations. In contrast, the Arts sector shows signs of crowding out, where increased government support appears to substitute for private giving. Overall, the chapter highlights the complex and field-specific ways in which public funding strategies interact with macroeconomic conditions. Chapter Three shifts the focus to the spatial and temporal dynamics of charity entry and exit across Census Subdivisions. It examines how neighbourhood-level socio-economic conditions - such as poverty rates, expectations of government support, and the existing charity landscape - influence where and when charities form or close. Using a Poisson Pseudo Maximum Likelihood model with high-dimensional fixed effects, the analysis finds that charity entry is positively associated with local poverty and anticipated funding, particularly in need-responsive sectors like Relief of Poverty and Education. Exit, by contrast, is more closely tied to prior funding shortfalls. The chapter also identifies patterns of complementarity and substitution across charity types and shows that charities serving remote or underserved areas are more likely to enter in response to local needs. More broadly, the analysis reveals a mix of coordination and competition in both entry and exit dynamics. Extending the analysis to include a macroeconomic focus to tie into the earlier chapters, the chapter shows that charity entry and exit decisions respond to broader economic conditions, offering a macro-geographic perspective on the charitable sector.
Keywords: charitable giving by fields; Business cycles; macroeconomic conditions; giving amounts; government funding to charities by fields; funding to charities from governments at different levels; charity entry and exit; poverty; inter-organisational competition and substitution; spatial analysis